Effect of ultrasound pre-treatment on formation of transglutaminase-catalysed soy protein hydrogel as a riboflavin vehicle for functional foods. (December 2015) - Hu, Hao; Zhu, Xinrong; Hu, Tan; Cheung, Imelda W.Y.; Pan, Siyi; Li-Chan, Eunice C.Y.
Highlights: TGase catalysed soy protein gels were used to encapsulate riboflavin (VB2 ). High intensity ultrasound (HIU) increased VB2 encapsulation efficiency and gel yield . HIU of SPI reduced swelling, erosion and VB2 release in simulated digestive fluids. 40 min HIU led to smaller and more uniform alveolate pores of the gels. HIU increased the TGase cross-linking interaction and the non-polar nature of gels. Graphical Abstract: Abstract: High intensity ultrasound (HIU) treated soy protein isolate (SPI) and non-HIU-treated SPI were cross-linked by transglutaminase to form hydrogels. SDS-PAGE showed that HIU increased the amount of high molecular weight aggregates, likely due to the formation of ε-(γ-glutamyl) lysine bonds. Moreover, HIU pretreatment increased the hydrophobic nature of transglutaminase gels as demonstrated by FT-Raman. HIU changed the 3D-network structure of transglutaminase induced SPI gel with riboflavin (TSGR). Furthermore, 40 min HIU increased gel yield, riboflavin encapsulation efficiency and gel strength of TSGR. HIU decreased swelling and protein erosion of TSGR in simulated gastrointestinal fluids. It also resulted in reduced riboflavin release rate and altered the release mechanism in simulated gastrointestinal fluids both in the absence and presence of digestive enzymes. In conclusion, HIU may facilitate covalent cross-linking, increase hydrophobicity and change the 3D network of TSGR, leading to differences in hydrogel stability, as well as riboflavin encapsulation and release profiles.